2022
DOI: 10.32394/rpzh.2022.0196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary components on intestinal short-chain fatty acids (SCFAs) synthesis in healthy adult persons following a ketogenic diet

Abstract: Background. The ketogenic diet (KD) has been used for almost 100 years in the treatment of drug-resistant epilepsy in children - and adults. The intestinal microbiome has a climax character, and the main factor changing its composition and functions is the diet. Both increased biodiversity and the production of short-chain fatty acids (SCFAs) are important indicators of gut barrier function. SCFAs are synthesized by microorganisms through the fermentation of dietary fibre provided with the diet. They are an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Recently, probiotics that produce butyrate have been widely used in aquaculture ( 36 ). Microbial community composition and metabolism are significantly related to the content and composition of SCFAs in the intestine, especially butyric acid ( 37 39 ). C. butyricum produces butyric acid, which can improve the balance of the host intestinal flora and reduce the probability of intestinal infection with pathogenic bacteria ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, probiotics that produce butyrate have been widely used in aquaculture ( 36 ). Microbial community composition and metabolism are significantly related to the content and composition of SCFAs in the intestine, especially butyric acid ( 37 39 ). C. butyricum produces butyric acid, which can improve the balance of the host intestinal flora and reduce the probability of intestinal infection with pathogenic bacteria ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…While specific studies indicated notable rises in total SCFAs after dietary fiber intervention, others observed no significant alterations, indicating that the influence of nutritional fibers on SCFA levels may be influenced by variables such as dosage, fiber type, and baseline gut microbiota composition [391,392]. To analyze the potential mechanisms of the role of the ketogenic diet in epilepsy, a recent study by Gudan et al examined the impact of this on the synthesis of intestinal SCFAs in healthy adults [393]. The analysis highlighted that cruciferous and leaf vegetables, berries, and nuts consumption on a ketogenic diet have been linked to a positive impact on the profile of SCFAs.…”
Section: Dietary Interventionmentioning
confidence: 99%
“…While specific studies indicated notable rises in total SCFAs after dietary fiber intervention, others observed no significant alterations, indicating that the influence of nutritional fibers on SCFAs levels may be affected by variables such as dosage, fiber type, and baseline gut microbiota composition [375,376]. To analyze the potential mechanisms of the role of the ketogenic diet in epilepsy, a recent study by Gudan et al, examined the impact of this on the synthesis of intestinal SCFAs in healthy adults [377]. The analysis highlighted that cruciferous and leaf vegetables, berries, and nuts consumption on a ketogenic diet have been linked to a positive impact on the profile of SCFAs.…”
Section: Dietary Interventionmentioning
confidence: 99%